[LB.03.10] METABOLOMICS PROFILING OF SERUM ELECTROLYTES SHOW A FATTY ACID ENRICHMENT FOR SERUM POTASSIUM LEVELS. (September 2017) - Menni, C.; McCallum, L.; Zierer, J.; Spector, T.D.; Padmanabhan, S.
Abstract : Objective: Electrolytes have a crucial role in maintaining health and their serum levels are homeostatically maintained within a narrow range by multiple pathways usually involving the kidneys. Sodium is the major extracellular cation and changes in sodium levels affect blood pressure plasma and interstitial volumes. Potassium is the main intracellular cation and plays a key role in maintaining resting membrane potential. Changes in plasma potassium levels can disrupt cardiac conduction and cause sudden death. Proteins, phospholipids, cholesterol, and neutral fats account for 90% of the mass of solutes in plasma and it is unclear whether levels of these non-electrolytes have an impact on free serum electrolyte concentrations. We used metabolomic profiling to discover molecular markers and pathways associated with serum electrolytes levels that could be of therapeutic use. Figure. No caption available. Design and method: 1523 adults from TwinsUK not on BP lowering therapy and without renal impairment were included in the analysis of 592 fasting plasma metabolites (Metabolon Inc). We looked for metabolites associated with chloride, sodium, potassium and bicarbonate by running linear mixed models adjusting for age, BMI, gender, family relatedness and multiple comparisons using Bonferroni correction. For each electrolytes, we further performed pathway enrichments analysis using the PAGE algorithm implemented in the R-package piano. Results: Chloride, potassium, bicarbonate and sodium correlated with 10, 58, 36 and 17 metabolites respectively (each P < 2.1 × 10[−5]). Among the top metabolites associated with serum potassium levels are fumarate (Beta(SE) = −0.07(0.008, P = 7.24 × 10[−16]), an intermediate in citric acid cycle, the long chain fatty acid myristoleate (14:1n5) (−0.06(0.008), P = 1.97 × 10[−14]), and the monohydroxy fatty acid 3-hydroxydecanoate (−0.04(0.008), P = 1.24 × 10[−6]), inversely associated with both serum potassium and with gut microbiome diversity (Shannon diversity: −0.08(0.03), P = 0.01). Top association for chloride, sodium and bicarbonate include threonate, cystathionine and glutamine respectively. Enrichment analysis is presented in Figure 1. Potassium is significantly down-regulated by fatty acids including acylcarnitine, long and medium chain, monohydroxy, dicarboxylate and polyunsaturated, while its serum levels appear upregulated by lysolipids, phospholipids, sphingolipid and steroids. Conclusions: We identified metabolic pathways that correlate with serum electrolytes levels and the role of these metabolic pathways on electrolyte homeostasis merits further studies.